1986
DOI: 10.1111/j.1748-5827.1986.tb02255.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic anatomy of the canine liver: simple measurements determined from the lateral radiograph

Abstract: The literature on plain film evaluation of the canine liver is reviewed and the problems associated with radiographic hepatometry in this species and in man are outlined. Methods used to determine liver size in man are briefly described. Liver measurements obtained from lateral recumbent radiographs of 20 German Shepherd Dogs were examined statistically. The ratio of a measurement of liver length to second lumbar vertebra body length was found to be of statistical value, as was the relative position of the jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…One previous study reported evidence that excessive fat deposition in the falciform ligaments may result in dorsal deviation of the liver parenchyma in cats . Elongation of the triangular ligament in older cats may result in caudal and dorsal extension of the liver, which can also be misdiagnosed as hepatomegaly . In our clinical experience, dorsal deviation of the liver in obese cats without liver disease has often been misdiagnosed as microhepatia.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…One previous study reported evidence that excessive fat deposition in the falciform ligaments may result in dorsal deviation of the liver parenchyma in cats . Elongation of the triangular ligament in older cats may result in caudal and dorsal extension of the liver, which can also be misdiagnosed as hepatomegaly . In our clinical experience, dorsal deviation of the liver in obese cats without liver disease has often been misdiagnosed as microhepatia.…”
Section: Introductionmentioning
confidence: 66%
“…Changes in hepatic size are frequently used as indicators of liver disease . Hepatic vascular stasis, steroid hepatopathy, hepatic lipidosis, inflammatory, and infiltrative disease, and neoplasia are differential diagnoses of hepatomegaly, and hepatic lipidosis is one of the most common liver diseases in cats .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations